Predictive Value of Cervical Length Measurement and Fibronectin Testing in Threatened Preterm Labor. Issue 2 (June 2015) - van Baaren, G.J.; Vis, J.Y.; Wilms, F.F.; Oudijk, M.A.; Kwee, A.; Porath, M.M.; Oei, G.; Scheepers, H.C.; Spaanderman, M.E.; Bloemenkamp, K.W.; Haak, M.C.; Bolte, A.C.; et al.
<x xml:space="preserve">Abstract</x> (Obstet Gynecol. 2014;123(6):1185–1192)